Aesthetic oral rehabilitation with narrow implant in a patient with dental agenesia: Case report (Research, Society and Development, 2023)
The search for aesthetics and better functional conditions brought advances in oral rehabilitation for the most varied cases and their particularities, such as the narrow diameter implant, which allows rehabilitation in areas that were previously unfeasible, due to space limitations, thus making it impossible to use a conventional implant. As well as the evolution of the materials of single crowns, which currently make it possible to reconcile aesthetics and strength, characteristics present in ceramics reinforced with lithium disilicate. The objective of this case repor tis to report the clinical step of an oral rehabilitation in a patient with tooth agenesis through a single crown in lithium disilicate on an implant with a narrow diameter in the anterior region referring to dental unit 22. Therefore, rehabilitation treatment was indicated. that best suited the individual needs of the case presented. Finally, the patient was satisfied with the treatment performed, in which it was possible to reconcile functional and aesthetic rehabilitation, considerably improving the harmony of the smile.